Inventarisasi Jenis-Jenis Begonia di Pekarangan Masyarakat Kota Pontianak - Riyati, Indri; Linda, Riza; Ifadatin, Siti (Program Studi Biologi, Fakultas Teknik, Universitas Samudra, 2023)
Begonia is flowering plant and member of the Begoniaceae Family. Begonia has spesific characteristics such as herb plants, shrub or vine, a watery trunk, and an asymmetric leaf. The purpose of this research is to identify the species of Begonia where found in the community courtyards in Pontianak city. This research has been done on June to July 2022. The Begonia sample collected in courtyard community in Pontianak city by a method of direct observation. Identification of Begonia based on the characteristic of morphology in guide book with the title “Begonias cultivation, identification, and natural history”. The result of this research is found 19 species of Begonia such as Begonia auriculata, Begonia acetosa, Begonia aconitifolia, Begonia stipulaceae, Begonia erythrophylla, Begonia abel carriere, Begonia sp., Begonia cucullata, Begonia cucullata, Begonia heracleifolia, Begonia heracleifolia, Begonia masoniana, Begonia grandis, Begonia handelii, Begonia argenteo gutata, Begonia cucullata, Begonia rex, Begonia manaus, Begonia fimbristipula.